Impact of Spousal Loss on The Self-Esteem of Older Adults - Nur Meliza; Nissha Ayu Nur Azizha; Muhammad Ari Arifianto; Sri Widowati; Nurilla Kholidah (Caring: Indonesian Journal of Nursing Science, 2025)
Spousal loss is one of the most profound life events in old age, often accompanied by psychological challenges such as loneliness, depression, and reduced self-esteem. Self-esteem plays a vital role in older adults’ mental health, influencing their ability to adapt to aging and cope with bereavement. This study aimed to examine the relationship between spousal loss and self-esteem among older adults. A correlational quantitative design with a cross-sectional approach was employed. A total of 87 older adults were recruited using purposive sampling. Data collection was conducted from March to April 2023 using the Rosenberg Self-Esteem Scale (RSES) questionnaire. Data were analysed using univariate analysis and bivariate analysis with the chi-square test. The average age of the respondents was 66 years. Most participants were female, of Javanese ethnicity, Muslim, residing in Malang City, had low educational attainment (elementary school), worked in the private sector, and were in stable health condition. The analysis revealed a significant association between spousal loss and self-esteem among older adults (p-value < 0.0001). Self-esteem in older adults is associated with the presence of a spouse. Those who still have a living spouse tend to exhibit higher levels of self-esteem. Psychosocial interventions, as well as family and community support, are essential to enhance self-acceptance and self-esteem among older adults who have experienced spousal loss. Keyword: Older adults, Spousal loss, Self-esteem, Widowhood, Psychosocial well-being